ET-Network Regional Training Workshop Tunis, December 6-9, 2019 - Gamal, R. (2021)
There are several online databases as well as algorithms exist to map the actual evapotranspiration (ETa) in time and space. However, these data basis and algorithms are based on equations using complex land-plant-atmosphere interactions. Before using these databases and algorithms to map Eta, there is a strong need to understand the theory on which ETa is mapped. Further, there is a strong need to validate the results of these remote sensing derived Eta measurements. Therefore, there is a dire need to build the capacity of the local institutions who are end user of these products. If they are not able to map the Eta, at least they should understand the basis of these maps. Further, the local institutions should have not only physical infrastructure to validate the remote sensing derived ETa products but also fully understand how Eta is measured from these instruments. Keeping this in mid, ICARDA organized a four days training in Tunis. In this training, ET experts from Jordan, Egypt, Tunis, Lebanon and Morocco participated. The participants were trained on ET measurements using energy balance methodologies with a special focus on Cordoba-ET system, the CORDOVA-ET system, data collection, analysis and dissemination as a standardized validation protocol as well as from the other field ETa methods of determination. Detail of the training program is given in Annex-I.